CRISPR/Cas9‐targeted mutagenesis of TaDCL4, TaDCL5 and TaRDR6 induces male sterility in common wheat. Issue 4 (23rd January 2023) - Zhang, Rongzhi; Zhang, Shujuan; Li, Jihu; Gao, Jie; Song, Guoqi; Li, Wei; Geng, Shuaifeng; Liu, Cheng; Lin, Yanxiang; Li, Yulian; Li, Genying
Summary: Phased, small interfering RNAs (phasiRNAs) are important for plant anther development, especially for male sterility. PhasiRNA biogenesis is dependent on genes like RNA polymerase 6 (RDR6), DICER‐LIKE 4 (DCL4), or DCL5 to produce 21‐ or 24 nucleotide (nt) double‐strand small RNAs. Here, we generated mutants of DCL4, DCL5 and RDR6 using CRISPR/Cas9 system and studied their effects on plant reproductive development and phasiRNA production in wheat. We found that RDR6 mutation caused sever consequence throughout plant development starting from seed germination and the dcl4 mutants grew weaker with thorough male sterility, while dcl5 plants developed normally but exhibited male sterility. Correspondingly, DCL4 and DCL5, respectively, specified 21‐ and 24‐nt phasiRNA biogenesis, while RDR6 contributed to both. Also, the three key genes evolved differently in wheat, with TaDCL5‐A/B becoming non‐functioning and TaRDR6‐A being lost after polyploidization. Furthermore, we found that PHAS genes (phasiRNA precursors) identified via phasiRNAs diverged rapidly among sub‐genomes of polyploid wheat. Despite no similarity being found among phasiRNAs of grasses, their targets were enriched for similar biological functions. In light of the important roles of phasiRNA pathways in gametophyte development, genetic dissection of the function of key genes may help generate male sterile lines suitable for hybrid wheat breeding.